Pengembangan Obyek Wisata Pantai Katembe Desa Madongka Kabupaten Buton Tengah - Ahmad Syahrul; Syahriar Tato; Ilham Yahya (Journal of Urban Planning Studies, 2021)
Abstrac Ahmad Syahrul, 2020. "Development of Katembe Beach Tourism Object, Madongka Village, Central Buton Regency". Thesis of Urban and Regional Planning Study Program, Faculty of Engineering, Bosowa Makassar University. (Supervised by Dr. Ir. Syahriar Tato, MS. MH and Ilham Yahya ST, MSP). This study aims to determine the potential development of Katembe Beach tourism objects as a tourist area, by identifying existing potentials and strategies that will be applied in developing these tourism objects as coastal tourism destinations that can attract tourists. The analysis method used is; Quantitative Analysis and Weighting. From the analysis, that the area has the potential to be developed. Some of the development directions that can be used are utilizing all the natural potentials that are beautiful, charming, varied in an unspoiled environment, and exploiting the potential that exists in the community as a form of support in developing tourist areas. Keywords: Katembe Beach Tourism Object Development